The Generalisations of n-Cutting Sites Splicing Languages via Yusof-Goode Splicing System using a Non-Palindromic Rule and Crossing Site - Nooradelena, Mohd Ruslim; Yuhani, Yusof; Mohd Sham, Mohamad; Mohd Firdaus, Abdul-Wahab; Mudaber, Mohamad Hassan (UTM Press, 2024)
Yusof-Goode (Y-G) splicing system was introduced in the context of Formal Language Theory. Splicing system is a dry model that presents enzymatic activities between initial strings and restriction enzymes, while splicing language is the generated strings from the splicing system. Splicing language will yield either as new molecules or initial string itself, and can be either in adult or inert, limit or transient languages. In this paper, some mathematical results on generating and generalising the n-cutting sites splicing languages are established using a Y-G splicing system consisting of a single pattern of strings with non-palindromic rule and crossing site. Two lemmas are presented to discuss the Y-G splicing system when two and three cutting sites exist in a single pattern of string. Different characteristics concerning the features of left and right contexts are established. A theorem is then proposed based on the lemmas to generalise the n-cutting sites splicing languages resulting from a Y-G splicing system with a single pattern of string and a non-palindromic rule when n-cutting sites exist in a single pattern of string.